2013
DOI: 10.1073/pnas.1213867110
|View full text |Cite
|
Sign up to set email alerts
|

Plant mating system transitions drive the macroevolution of defense strategies

Abstract: Understanding the factors that shape macroevolutionary patterns in functional traits is a central goal of evolutionary biology. Alternative strategies of sexual reproduction (inbreeding vs. outcrossing) have divergent effects on population genetic structure and could thereby broadly influence trait evolution. However, the broader evolutionary consequences of mating system transitions remain poorly understood, with the exception of traits related to reproduction itself (e.g., pollination). Across a phylogeny of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
74
3
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(81 citation statements)
references
References 68 publications
3
74
3
1
Order By: Relevance
“…Our comparison of defence related traits and palatability to generalist herbivore caterpillars of M. brassicae did not reveal any differences between selfing and outcrossing populations, and thus provides no support for the hypothesis that selfing populations should be more susceptible to generalist herbivores (Johnson et al 2009). Although herbivore damage induced changes in trichome density and SLA, our data do not support the prediction that selfing populations should have a higher inducible resistance (Campbell and Kessler 2013).…”
Section: Resultscontrasting
confidence: 54%
See 4 more Smart Citations
“…Our comparison of defence related traits and palatability to generalist herbivore caterpillars of M. brassicae did not reveal any differences between selfing and outcrossing populations, and thus provides no support for the hypothesis that selfing populations should be more susceptible to generalist herbivores (Johnson et al 2009). Although herbivore damage induced changes in trichome density and SLA, our data do not support the prediction that selfing populations should have a higher inducible resistance (Campbell and Kessler 2013).…”
Section: Resultscontrasting
confidence: 54%
“…Rather than looking at defence traits individually, using a generalist herbivore (folivore) provides an integral test for differences in traits associated with nutritional quality (Agrawal 2000;Campbell and Kessler 2013). Our feeding trial indicated that M. brassicae caterpillar weight gain was not affected by population or mating system, which does not support the macro evolutionary hypothesis that selfing should frequently result in evolution of increased susceptibility to generalist herbivores (Johnson et al 2009).…”
Section: Constitutive Differences In Traits Related To Plant Defencecontrasting
confidence: 46%
See 3 more Smart Citations